PENGEMBANGAN MEDIA TANGRAM DIGITAL TERHADAP PEMAHAMAN KONSEP MATEMATIKA PADA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Aufa Dhiya Ulhaq; Aziz Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Understanding concepts is the main foundation in mathematics learning, especially in the composition and decomposition materials of flat buildings. However, students often have difficulty in imagining the process of compilation (composition) and decomposition (decomposition) building into simpler parts. This research was conducted to develop digital tangram media, measuring its effectiveness and influence on the understanding of concepts of grade IV students. The limited field trial was carried out at MI Negeri 1 Banyumas. The method used is Research and Development (R&D) with a media product development model in the form of ADDIE (Analysis, Design, Development, Implementation, Evaluation). The type of research used is quasi-experimental. To test the influence of digital tangram media, it was carried out by comparing the average value of the posttest between the experimental class that used digital tangram media and the control class that studied without the media. Data analysis used a t-test to determine the difference in average value results and an N-Gain test was used to measure the effectiveness of the use of digital tangram media. The results of the statistical test showed a significance value of 0.00 < 0.05, which proved the difference in the average value between the experimental class and the control class. Furthermore, the N-Gain test obtained an average score of 60%, which is classified as quite effective. Based on these findings, it can be concluded that the digital tangram media developed has proven to be quite effective and has an influence on the understanding of mathematics concepts in grade IV students who were tested at MI Negeri 1 Banyumas.